(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
The present study was carried out to advance towards the conserving threatened forest tree species of Bangladesh under ex-situ conservation system. Four thousand plants of forty eight threatened forest tree species were conserved at three areas, namely Institute of Forestry and Environmental Sciences, Chittagong University; Radar Unit of Bangladesh Air Force, Cox‟s Bazar; and the Keochia research station of Bangladesh Forest Research Institute. The average 90-95% plants survived in each conservation site and the maximum average plant height was recorded as 4.0m after two years of plantation. It will provide a wider buffer for the protection of the forest gene resources. J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(2): 89-98